Penerapan Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) Berbasis Liveworksheets Untuk Meningkatkan Minat Belajar PKN Siswa Kelas IV SDIT Muhammadiyah 01 Kotapinang - Nurhabibah Harahap; Deprizon Deprizon; Wismanto Wismanto; Radhiyatul Fithri; Salman Salman; Sakban Sakban (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research is motivated by the low interest of students in learning Civics subjects because students feel bored, fed up with learning carried out using the lecture method so that students are not interested in participating in learning. This study aims to increase the interest of fourth grade students of SDIT Muhammadiyah 01 Kotapinang in Civics subjects by implementing a cooperative learning model of the TGT (Team Games Tournament) type based on liveworksheets. This research is a classroom action research (PTK). The subjects in this study were 15 fourth grade students of SDIT Muhammadiyah 01 Kotapinang. While the object of this research is the application of the TGT (Team Games Tournament) learning model based on liveworksheets media to increase students' interest in learning. This research was conducted in two cycles, each cycle was carried out for two meetings. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results of the study on the application of the TGT learning model based on liveworksheets in the Civics subject of class IV SDIT Muhammadiyah 01 Kotapinang are that in cycle I, teacher activity was 81.25% in the good category, student activity was 71.25% in the sufficient category and student learning interest was 72.91% in the sufficient category. In cycle II, the results of the application of the TGT model based on liveworksheets increased, teacher activity was 96.25% in the very good category, student activity was 91.25% in the very good category and student learning interest was 92.91% in the very good category. The results of this study indicate that the application of the TGT (Team Games Tournament) type cooperative learning model based on liveworksheets in class IV SDIT in Civics subjects can increase student learning interest.